Gremlin 1 depletion in vivo causes severe enteropathy and bone marrow failure. Issue 2 (28th May 2020) - Rowan, Simon C; Jahns, Hanne; Mthunzi, Liberty; Piouceau, Lucie; Cornwell, Joanna; Doody, Róisín; Frohlich, Stephen; Callanan, John J; McLoughlin, Paul
Abstract: The intestinal epithelium is perpetually renewed from a stem cell niche in the base of crypts to maintain a healthy bowel mucosa. Exit from this niche and maturation of epithelial cells requires tightly controlled gradients in BMP signalling, progressing from low BMP signalling at the crypt base to high signalling at the luminal surface. The BMP antagonist gremlin 1 ( Grem1 ) is highly expressed by subepithelial myofibroblasts adjacent to the intestinal crypts but its role in regulating the stem cell niche and epithelial renewal in vivo has not been explored. To explore the effects of Grem1 loss in adulthood following normal growth and development, we bred mice ( ROSA26CreER‐Grem1 flx/flx ) in which Grem1 could be deleted by tamoxifen administration. While Grem1 remained intact, these mice were healthy, grew normally, and reproduced successfully. Following Grem1 depletion, the mice became unwell and were euthanised (at 7–13 days). Post‐mortem examination revealed extensive mucosal abnormalities throughout the small and large intestines with failure of epithelial cell replication and maturation, villous atrophy, and features of malabsorption. Bone marrow hypoplasia was also observed with associated early haematopoietic failure. These results demonstrate an essential homeostatic role for gremlin 1 in maintaining normal bowel epithelial function in adulthood, suggesting that abnormalities in gremlin 1 expression can contribute to enteropathies. We also identified a previously unsuspected requirement for gremlin 1 in normal haematopoiesis. © 2020 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.